Generation of a novel germline stem cell line expressing a germline‐specific reporter in the mouse. Issue 7 (3rd May 2013) - Shiura, Hirosuke; Ikeda, Rieko; Lee, Jiyoung; Sato, Takuya; Ogonuki, Narumi; Hirose, Michiko; Ogura, Atsuo; Ogawa, Takehiko; Abe, Kuniya
<x xml:space="preserve">Abstract</x> Germline stem (GS) cells are stem cell lines derived from postnatal male germline cells. Remarkably, GS cells can form functional spermatozoa when transplanted into infertile host mouse testes, indicating that GS cells have spermatogonial stem cell (SSC) activity. As GS cells are the only type with SSC activity, they are most suitable for in vitro studies on male germ cell differentiation. However, GS cells can deviate from the germ cell state to become other types of cells, depending on culture conditions. Therefore, it is desirable to have a monitor system to ensure that GS cells are kept at the germ cell state in culture. Here, we established GS cell lines from neonatal testes of transgenic mice that express the fluorescent protein, Venus, whose gene expression is driven by the promoter of Mvh (mouse Vasa homolog), a gene highly specific to mammalian germ cells. This novel cell line has genuine GS cell properties equivalent to existing GS lines, including the ability to generate viable offspring. This Mvh–Venus GS cell line, to our knowledge, is the first one expressing a germ cell‐specific reporter. This valuable resource should provide new opportunities for studies on male germ cell differentiation. genesis 51:498–505. © 2013 Wiley Periodicals, Inc.